From "Thin" Familiarity to "thick" strangeness: Thinking the Other in The Journey of Van Nguyen - Avieli, Nir; Lerner, Julia (Hagar: Studies in Society and Culture, 2008)
In many ways, this scene captures the essence of the paradox in which the Vietnamese "boat people" who found refuge in Israel in the late 1970s are locked: a small group of people forcibly thrown from their war-torn homeland to a very different part of the world, only to find themselves dapped in another violent conflict, one that has outlasted the war in Vietnam and seems to be going on forever. The Journey of Van (and not "Vaan," a failed attempt at capturing the tonal nature of Vietnamese without using diacritical marks) touches on many aspects of modern migration: it is about the social category of migrants and its lived, experienced phenomenology; it is about the relationship between migrants and the "old country"; it is about "migrants’ time," which oscillates between the past and present and often lacks future; it is about Vietnam and its love-hate relationship with the huge Vietnamese diaspora; and it is also about Israel and Israeliness, and about the failed Israeli attempt to naturalize migrants, as opposed to the ’absorption’ Jewish olim.